Mixed Methods in Business, Management and Accounting Research: an Experimental Design in the Entrepreneurship Domain (European Journal of Interdisciplinary Studies, 2022)
All research strategies suffer from some weaknesses. Combining qualitative and quantitative approaches might offset some flaws. Recently a growing methodological trend arose from the acknowledgement that mixed methods may increase the value of several research projects. With this background, the paper analyses trends of mixed methods in the business, management and accounting area during the last twenty years. The analysis highlights domains where mixed methods are not frequently used, such as entrepreneurship, and presents ongoing research based on mixed methods on the Italian community enterprises, a set of collective entrepreneurial initiatives working for sustainable regeneration in their territories. These enterprises are elusive since they are neither easily identifiable nor extractable from databases. A fixed and sequential mixed method approach turns out to be effective for investigating these evolving enterprises. The work is relevant for novices to mixed methods research and provides meaningful insights to analyze a type of organisation that is very important in depleted contexts.